2010
DOI: 10.1177/0011000010378612
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline to Preparation to Advancement: Graduates’ Experiences In, Through, and Beyond Leadership Preparation

Abstract: Purpose: The purpose of the study was to describe the nature of preparation among a nonpurposeful sample of 17 leadership preparation programs and to investigate the relationship of their participants’ characteristics, program experiences, leadership learning, and initial career outcomes. The study was guided by prior research on innovative programs (Darling Hammond, Meyerson, La Pointe, & Orr, 2009; Leithwood, Jantzi, Coffin, & Wilson, 1996). Data Collection and Analysis: Faculty members from 13 insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(181 citation statements)
references
References 34 publications
6
169
0
6
Order By: Relevance
“…In addition, research has indicated that preparation programs located in doctoral and research institutions simply have more institutional capacity to prepare leaders effectively than other institutions (Baker, Orr, & Young, 2007). Furthermore, principals from preparation programs located at doctoral and research institutions were more likely to become employed as school leaders and had faster rates of career advancement than those from other preparation programs, suggesting differences in principal effectiveness (Fuller & Orr, 2006;Orr, 2011).…”
Section: Principal Preparation Teacher Selection and Teacher Qualifmentioning
confidence: 99%
“…In addition, research has indicated that preparation programs located in doctoral and research institutions simply have more institutional capacity to prepare leaders effectively than other institutions (Baker, Orr, & Young, 2007). Furthermore, principals from preparation programs located at doctoral and research institutions were more likely to become employed as school leaders and had faster rates of career advancement than those from other preparation programs, suggesting differences in principal effectiveness (Fuller & Orr, 2006;Orr, 2011).…”
Section: Principal Preparation Teacher Selection and Teacher Qualifmentioning
confidence: 99%
“…A broader scope of methodological tools have been used to examine the quality and effectiveness of educational leadership preparation programs by conducting program evaluations using survey (Buskey & Karvonen, 2012;Orr, 2012) mixed methods (Huang et al, 2012); case study (Hernandez & McKenzie, 2010); and action research (Orr, Doolittle, Kottkamp, Osterman, & Silverberg, 2004). Also, survey design has been used in a general way to capture an overall picture of faculty who teach in educational leadership preparation programs (Hackmann & McCarthy, 2011), while Rusch (2004) used survey design more specifically to hone in on faculty's perceptions and discourse about gender and race in educational leadership classrooms.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…While important work has been done in schools of education (Creighton, Creighton, & Parks, 2010), research specific to educational leadership graduate students' gendered experiences is relatively sparse (Mansfield et al, 2010). While there are ongoing discussions evaluating educational leadership preparation programmatic quality (Orr, 2012), few scholars examine mentoring approaches (Sherman & Grogan, 2011). Importantly, researchers are increasingly calling for an expansion of intentional conversations concerning gender identity in educational leadership preparation programs (Killingsworth, Cabezas, Kensler, & Brooks, 2010;Mansfield et al, 2010), along with work that looks at gender and other identity complexities such as race/ ethnicity within academe as a whole (Davis, 2008;Harden, Clark, Johnson, & Larson, 2009;Mansfield et al, 2010;Reddick, 2011;Schlosser & Foley, 2008).…”
mentioning
confidence: 99%
“…A greater awareness of impact and outcome measures has guided conversations around these grants in recent years. The 2011The , 2012 national conferences sponsored by the School Leadership Program Communication Hub (now School Leadership Preparation and Development Network [SLPDN]) dedicated a significant amount of time to program evaluation and the impacts of the program features. The SLPDN is an organization that connects all current and past SLP grantees in a variety of ways, including through national conferences, webinars, and collaborative research and publications.…”
Section: Setting the Context: The Slpmentioning
confidence: 99%